Analisis Keterampilan Psikomotorik Mahasiswa Pada Praktikum Biokimia dan Korelasinya dengan Hasil Belajar Kognitif - Etika Dyah Puspitasari; Novi Febrianti (Jurnal Pendidikan Biologi, 2018)
Biochemistry practice is a basic practicum that must be mastered by biology education students. Skills in biochemistry practicums are the basis used in practicum physiology, genetics, microbiology, and other materials in biology. This study aims to analyze psychomotor skills achieved by students in biochemical practicums and examine the relationship between cognitive learning outcomes and psychomotor learning outcomes of biology education students in biochemical practicums, especially in the experimental material for making solutions and measuring pH. This research is a quantitative descriptive study with a sample of 40 biology education students. Learning outcomes data were analyzed using quantitative and qualitative analysis, and the correlation between psychomotor and cognitive learning outcomes was analyzed using Pearson Correlation analysis at α = 0.01. The results showed that psychomotor skills that were mastered by students in biochemistry practicum (making solutions and pH measurements) included levels 1-4, with an achievement percentage of 89.19% at level perception; 97.30% at the level set; 51.62% at the guided response level and 72.97% at the mechanism level, with psychomotor learning outcomes averaging 58 (sufficient category). The cognitive value of students in the experimental for making solutions and pH measurements was 63.32 (good category). There is a positive correlation between psychomotor and cognitive learning outcomes of students in biochemistry practicum (r = 0.67) with a strong correlation category.